Pasolini és a görög színház: Az Oresteia fordításától a hat tragédiáig - Lakó, Zsigmond (Studia Litteraria, 2022)
Present study focuses on a less researched field of Pasolini’s oeuvre, namely his works written for the theatre. is corpus also contains the so-called six tragedies, considered the peak of his dramatic achievement. My aim is to point out in what ways Pasolini integrates certain elements of the Greek myths and tragedies into his modern theatre, which tries to distinguish itself both from the bourgeois and the avant-garde theatre, furthermore, how these elements affect his choice of themes and dramaturgy. I attempt to identify those biographical points and important theoretical questions that led Pasolini to the Greek tragedy: from his Oresteia translation, through the six tragedies, to the appearance of such elements as the peripheries and Africa in his films, which can eventually lead to a post-colonial reading of his theatrical works.